Theorizing STEM Education in the 21st Century - George Fomunyam, Kehdinga (IntechOpen, 2020)
Theorising STEM Education in the 21st Century is a book that captures the essence of Science, Technology, Engineering and Mathematics and the intricacies of STEM education in the contemporary society. It explores STEM as an interdisciplinary field as well as the individual disciplines that make up STEM. This ensures the field of STEM as a whole is theorised. The book provides critical insight on STEM education from Cairo to Cape Town or from America to Indonesia. With a team of authors from universities across the world, the book is a vital contribution to critical scholarship on STEM education in contemporary times.